THE CONTINUAL FORMING AND CONTRIBUTION OF INFECTIVE JUVENILES PRODUCED VIA ENDOTOKIA MATRICIDA OF ENTOMOPATHOGENIC NEMATODES IN THE FAMILY OF STEINERNEMATIDAE AND HETERORHABDITIDAE - Baliadi, Yuliantoro; Kondo, E.; Yoshiga, T. (Indonesian Journal of Agricultural Science, 2009)
The non-feeding developmentally arrested infective juveniles (IJs)of entomopathogenic nematodes in the family of Steinernematidaeand Heterorhabditidae seek out a susceptible insect host and initiateinfections. The aim of the research was to examine the continualforming and contribution of IJs produced via endotokia matricida(IJs-EM) of Heterorhabditis bacteriophora, Steinernema glaseri,and S. carpocapsae. The research was conducted at the Laboratoryof Nematology of the Saga University, Japan (April 2001-April2002) and the Laboratory of Nematology of the IndonesianLegume and Tuber Crops Research Institute (June 2003-October2004). The nematode progenies were investigated using the greaterwax moth, Galleria mellonella, pre-inoculated with 50 IJs at 25Â°C.Results showed that three reproductive adult generations wereobserved at day 18th. There were 135,000, 128,000 and 133,000 IJsper insect cadaver produced in H. bacteriophora, S. glaseri and S.carpocapsae, respectively. Endotokia matricida contributed ahigher number of IJs than that of a normal mode of IJs production.The ratios are 81%, 28% and 64% for H. bacteriophora, S. glaseri,and S. carpocapsae of the IJs total production, respectively. Amongthe generations, the highest contribution of IJs was come from thethird adult generation bearing endotokia matricida, i.e., 63%, 24%and 51% for the three nematode species. Although the IJs-EMwere more transparent compared to the normal IJs, they weremorphologically similar. The results show that endotokia matricidahas a pivotal role in a species maintenance and survival strategyof entomopathogenic nematodes in extreme environmental conditions.